Thermal Memory and Thermal Induced Phase Transformation in Shape Memory Alloys - Adiguzel, O. (Springer, 2016)
Shape memory effect is a peculiar property exhibited by a series of alloy systems. This property is characterized by the recoverability of desired shape of the material at different conditions, and these alloys take place in a class of smart materials due to this property. Shape memory effect is based on martensitic transformation, which is a solid state phase transition and occurs on cooling the material from high temperature parent phase region. Martensitic transformations are first order diffusionless transitions and governed by changes in the crystal structure of the material at angstrom level. Copper based alloys exhibit this property in metastable beta-phase field, which have bcc-structures at high temperature. These alloys undergo two ordered transitions on cooling, and bcc structures turn into B2 (CsCl) or DO3 (Fe3Al) - type ordered structures. These ordered structures martensiticaly undergo the non-conventional complex layered structures on further cooling. The product phase has the unusual complex structures called long period layered structures such as 3R, 9R or 18R depending on the stacking sequences on the close-packed planes of the ordered lattice.
NATO Advanced Research Workshop on Nanomaterials for Security -- AUG 30-SEP 03, 2015 -- Odessa, UKRAINE
Keywords: Martensite